Analysis of the use of high-alert medications in the care transition in a public hospital (Health and Biosciences, 2026)
Care transition involves the transfer of responsibilities between different levels of care or inpatient units (IU) with the goal of ensuring continuity of care and patient safety. It is considered a critical moment in care, as it is associated with increased vulnerability to errors and adverse events related to medication use. Among the main risk factors are high-alert medications (HAMs), due to their high potential to cause significant harm to patients in the event of failures in the medication-use process. Despite international and national protocols guiding the rational use of HAMs, problems associated with their use persist, such as their use in IUs without adequate monitoring. In this context, the objective of this study was to evaluate the continuity of HAMs in the prescriptions of patients undergoing care transition after discharge from the Intensive Care Unit (ICU) and who were admitted to an IU in a public hospital in Espírito Santo. 102 prescriptions were analyzed, of which 34% (n=35) showed continuity of HAMs after admission to the IU. The most prevalent AVMs were tramadol (62%; n=24), followed by amiodarone, midazolam, and morphine, present in 8% (n=3) of prescriptions, respectively. The results highlight the importance of effective communication and medication reconciliation during care transitions, essential measures to reduce the risks associated with AVMs and promote patient safety.